Development and enactment of an EAL policy: improving provision at an international sixth form - Van Der Meer, L (2021)
This study investigates the development and enactment of an English as an additional language (EAL) policy at an international sixth form that was motivated by the lack of local and national guidance on how to provide for EAL pupils. The policy development process included training teachers on second language acquisition (SLA) processes, organising collaborative experiences with peers to share expertise, encouraging teachers to trial new EAL strategies, and having teachers consult on policy texts and strategies in workshops and meetings. Data from five different surveys and eight 45-minute peer observations were collected to investigate teachers’ criteria for effective implementation of an EAL policy, their experiences with the policy development process, and how the EAL strategies advocated in the policy were enacted in classrooms. Emergent themes from the survey data measuring teachers’ criteria revealed that clear communication, formal implementation, and ensuring policy is applicable to the local context are required for effective implementation of EAL policy. Furthermore, teachers’ experiences with the policy development process were predominantly positive, cooperative, educational, and illustrated a small improvement in their underlying understanding of SLA processes. Peer observations demonstrated that the key EAL themes of planning for language input, planning for language output, and treating first language as a fund of knowledge were all actively employed in the classroom. The promotion of reading however was lacking. Recommendations for school leadership include encouraging wider participation with EAL strategies, formal implementation of EAL provision into schemes of work, appraisals, and observations, and to consider reading interventions. Furthermore, the wider educational community should consider integrating the EAL strategies used in this study into their own practice, and to address the paucity of research into teachers’ criteria for effective policy.